The Relationship Between Knowledge Level and Thermoluminescence Dosimetry (TLD) Use Behavior Among Radiographers in a Clinical Setting - Delfi Iskardyani; Muhammad Sofyan (Al-Hijrah Indonesia, 2026)
The increasing use of ionizing radiation in medical imaging requires proper monitoring to ensure the safety of radiographers, particularly through the use of Thermoluminescent Dosimeters (TLD). However, inconsistencies in knowledge and behavior regarding TLD usage may affect radiation protection practices. This study aims to determine the relationship between knowledge level and radiographers' behavior regarding the use of TLD. This research used a quantitative analytic design with a cross-sectional approach, involving 28 respondents at the clinical practice sites of the Diploma in Radiography at Adisutjipto Yogyakarta Indonesian Air Force Health Polytechnic. Data were collected using a structured questionnaire consisting of knowledge and behavior variables. The sampling technique used was convenience sampling, and data were analyzed using univariate and bivariate analysis with the Chi-square test. The results showed that the majority of respondents had good knowledge (64.3%) and good behavior (64.3%). A statistically significant relationship was found between knowledge and behavior (p < 0.05). These findings indicate that higher knowledge levels are associated with better compliance in TLD usage, although some inconsistencies remain in technical and procedural aspects. In conclusion, improving knowledge can positively influence behavior; therefore, continuous training, supervision, and reinforcement of radiation safety practices are recommended to enhance compliance in TLD usage.